ANALISIS PENGARUH PENEMPATAN PADA BANK INDONESIA, PEMBIAYAAN MURABAHAH DAN RASIO NON PERFORMING FINANCING TERHADAP LIKUIDITAS BANK UMUM SYARIAH (Studi Empiris pada Bank Umum Syariah di Indonesia Tahun 2013-2017) - Shafira Aulia; Jaka Isgiyarta (Diponegoro Journal of Accounting, 2019)
The purpose of this study is analyzing the effect of placements at Bank Indonesia, murabaha  financing and the ratio of non-performing financing to the liquidity of Sharia Commercial Banks in Indonesia. Liquidity is one indicator of measurement to determine the health assessment of Sharia Banks in Indonesia. This analysis uses Financing to Deposit Ratio (FDR) as an indicator of measuring liquidity. The type of data used in this study is secondary data and the total number of samples in this study were 55 data on Sharia Commercial Banks in Indonesia. The sampling method in this study uses purposive sampling technique with the criteria of Sharia Commercial Banks which published quarterly financial statements in 2013-2017. Placements in Bank Indonesia, murabahah financing and the ratio of non-performing financing variables were analyzed using multiple linear regression. The results of this study indicate that placements in  Bank Indonesia has a significant negative impact on FDR. While murabaha financing and the ratio of non-performing financing have a positive but not significant effect to FDR. Placement in Bank Indonesia, murabahah financing and the ratio of non-performing financing variables have a significant effect on the liquidity of Sharia Commercial Banks simultaneously.